Pest Control Devices - Frederick M. Fishel (EDIS)
PI229, a 3-page illustrated fact sheet by Frederick M. Fishel, explains the difference between a pest control device and a pesticide. Includes additional sources of information. Published by the UF Department of Agronomy, June 2010.